THE IMPORTANCE OF MARKETING IN HELPING COMPANIES WITH THEIR GROWTH STRATEGIES: THE CASE OF FOOD INDUSTRY IN KOSOVO - Ejup Fejza; Alban Asllani (European Scientific Journal, ESJ, 2013)
Marketing is one of the main departments within an organization and its duty is to identify customer needs and wants and to produce or modify products in attempt to respond to market demand. Often it is found that the marketing department will work with the management in order to meet the market demand, create new markets and in many cases satisfy consumers’ wants. It can be considered as the bridge between satisfying consumers and the management in attempt to create profit for the company. The main purpose of the research is to analyze the growth strategies of food producers in Kosovo and to provide clear recommendations for companies in developing their products, penetrate or develop new markets or niches.During the research the paper finds that most of the producers we have analyzed have not yet developed nor established a marketing department, and in many case most of them are missing a marketing or sales personnel. According to our data, only 45% of companies, (thirteen out of thirty, part of this study), have an established marketing department or have hired someone to work as head of marketing. This is a sign that food producers still do not see marketing as core function in their activities. They think more about productivity than sales and marketing. We find that the behavior of most companies is geared towards productivity and not so much towards marketing. Of course productivity is important, but marketing can help in increasing the sales, which could directly result to additional productivity needs.We also find out that there seems to be little courage in entering and exploring new markets; investing in offering new products to the market; or improving the design and quality of the products; and/or adding value to the existing products. Their growth strategies in terms of the above are still undeveloped. Therefore, there should be continuous insistence of